Lower Hemoglobin Concentration Is Associated with Retinal Ischemia and the Severity of Diabetic Retinopathy in Type 2 Diabetes - Alicia Traveset; Esther Rubinat; Emilio Ortega; Nuria Alcubierre; Beatriz Vazquez; Marta Hernández; Carmen Jurjo; Ramon Espinet; Juan Antonio Ezpeleta; Didac Mauricio (Journal of Diabetes Research)
Aims. To assess the association of blood oxygen-transport capacity variables with the prevalence of diabetic retinopathy (DR), retinal ischemia, and macular oedema in patients with type 2 diabetes mellitus (T2DM). Methods. Cross-sectional, case-control study (N=312) with T2DM: 153 individuals with DR and 159 individuals with no DR. Participants were classified according to the severity of DR and the presence of retinal ischemia or macular oedema. Hematological variables were collected by standardized methods. Three logistic models were adjusted to ascertain the association between hematologic variables with the severity of DR and the presence of retinal ischemia or macular oedema. Results. Individuals with severe DR showed significantly lower hemoglobin, hematocrit, and erythrocyte levels compared with those with mild disease and in individuals with retinal ischemia and macular oedema compared with those without these disorders. Hemoglobin was the only factor that showed a significant inverse association with the severity of DR [beta-coefficient = −0.52, P value = 0.003] and retinal ischemia [beta-coefficient = −0.49, P value = 0.001]. Lower erythrocyte level showed a marginally significant association with macular oedema [beta-coefficient = −0.86, P value = 0.055]. Conclusions. In patients with DR, low blood oxygen-transport capacity was associated with more severe DR and the presence of retinal ischemia. Low hemoglobin levels may have a key role in the development and progression of DR.